An unusual cause of secondary capillary leak syndrome in a child: rotavirus diarrhea - Aldemir-Kocabaş, Bilge; Karbuz, Adem; Ciftçi, Ergin; Demir, Meral; Ince, Erdal (The Turkish Journal of Pediatrics, 2013)
Secondary capillary leak syndrome is characterized by loss of fluid and proteins to the interstitial space due to different causes, which are related to endothelial damage. Rotavirus is the most common pathogen of diarrhea in childhood, especially during the first years of life. This virus is generally responsible for severe diarrhea and electrolyte imbalance in children. Some complications can also occur during the course of the rotavirus diarrhea. An eight-month-old girl with rotavirus diarrhea admitted to our clinic with severe dehydration. After restoring the intravascular volume, hypoalbuminemia and generalized edema were seen in the recruitment phase of the treatment, which was attributed to secondary capillary leak syndrome. She was successfully treated with prednisolone and discharged from the hospital without any sequelae. Herein, we report an infant with rotavirus diarrhea complicated with secondary capillary leak syndrome, which is an unidentified complication of the disease. To our knowledge, this is the first such case in the literature.